Analysis of structural integrity of a building using an artificial neural network artmap-fuzzy-wavelet - Lima, Fernando Parra Dos Anjos; De Souza, Simone Silva Frutuoso; Chavarette, Fábio Roberto [UNESP]; Lopes, Mara Lúcia Martins [UNESP]; Turra, Antonio Eduardo; Lopes, Vicente (Trans Tech Publications, 2014)
This paper presents an ARTMAP-Fuzzy-Wavelet artificial neural network to perform the analysis of the structural integrity of a building. The combination of Fuzzy ARTMAP neural network, wavelets transform to generate a tool that performs the identification and characterization of structural failure. This method is applied as a support tool for professionals in the inspection of mechanical and building structures to identify and characterize flaws in order to carry out preventive maintenance to ensure the integrity of the structure and decision making. In order to validate the methodology perform mathematical modeling of a building of two walk, and from this model were simulated different situations (base-line condition and improper conditions), yielding a database of signals that serve as input ARTMAP-Fuzzy-Wavelet neural network. The results obtained by ARTMAP-Fuzzy-Wavelet shown efficiency and robustness.
Keywords: Analysis of structural integrity; Artificial neural network; ARTMAP-Fuzzy-Wavelet; Building structure